Effect of catecholamine depletion and denervation on neuropeptide Y(NPY) and tyrosine-hydroxylase (TH) mRNA levels in rat sympathetic ganglia - Hänze, Jörg; Kummer, W.; Haass, Markus; Lang, R. E. (Experimental and clinical endocrinology & diabetes, 1994)
Thieme E-Books & E-Journals
Elektronische Reproduktion der Druck-Ausgabe 15. Juli 2009
Gesehen am 20.05.2025